VD_FINDINFO HC / 2011 / 554 vom 12. Oktober 2011 - VD Tribunal cantonal (2011)
BAIL À LOYER, DEMEURE DU DÉBITEUR, EXPULSION DE LOCATAIRE, LOGEMENT, LOYER, RÉSILIATION IMMÉDIATE | 257d CO, 308 al. 2 CPC (CH), 312 al. 1 CPC (CH)